-3t+9=t+9-4t

Simple and best practice solution for -3t+9=t+9-4t equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3t+9=t+9-4t equation:


Simplifying
-3t + 9 = t + 9 + -4t

Reorder the terms:
9 + -3t = t + 9 + -4t

Reorder the terms:
9 + -3t = 9 + t + -4t

Combine like terms: t + -4t = -3t
9 + -3t = 9 + -3t

Add '-9' to each side of the equation.
9 + -9 + -3t = 9 + -9 + -3t

Combine like terms: 9 + -9 = 0
0 + -3t = 9 + -9 + -3t
-3t = 9 + -9 + -3t

Combine like terms: 9 + -9 = 0
-3t = 0 + -3t
-3t = -3t

Add '3t' to each side of the equation.
-3t + 3t = -3t + 3t

Combine like terms: -3t + 3t = 0
0 = -3t + 3t

Combine like terms: -3t + 3t = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| (3-x)/(4-x)-4/3=0 | | 71.2=8(m+2.8) | | 2+c+1.4=c+2.4 | | 411010.8397+0.31x=x | | (0.2x-23)+(0.2x-53)=90 | | 4/7=x/18 | | -8(-x-6)=-6x-22 | | 2(3n+8)=0 | | (4x-4)/3x-6 | | -1-5b=14 | | 4x/7-(3x-13)/2=0 | | x^2-3/2x | | 12/7=x/14 | | 2b^2+11b+8=0 | | (2x-9)(3x+5)= | | 5x-7-(2x+11)=0 | | 63x+7y=6x+y | | 5/9[f-32]=c | | 1x/4=25 | | 3x+2x-5z=35 | | 3y+12=2y-27 | | 1/2(y-1)=1/3(y-4) | | 3x-16+17= | | 12t^2+28t-5= | | 1000(1)=70n-400 | | (4/Y^2)=2Y=12 | | 8x+9y=-18 | | 6×5-4/2 | | 2(6x/5) | | 9/4x+7=1/2-x | | x^2=200-y^2 | | 6×5_4/2 |

Equations solver categories